Signaling Toward Reactive Oxygen Species-Scavenging Enzymes in Plants - Dvořák, Petr; Krasylenko, Yuliya; Zeiner, Adam; Šamaj, Jozef; Takáč, Tomáš (Frontiers in Plant Science, 2021)
Reactive oxygen species (ROS) are signaling molecules essential for plant responses to abiotic and biotic stimuli as well as for multiple developmental processes. They are produced as byproducts of aerobic metabolism and affected by adverse environmental conditions. The ROS content is controlled on the side of their production, but also by scavenging machinery. Antioxidant enzymes represent a major ROS-scavenging force and are crucial for abiotic stress tolerance in plants. Enzymatic antioxidant defense occurs as a series of redox reactions for ROS elimination. Therefore, the deregulation of the antioxidant machinery may lead to the over-accumulation of ROS in plants, with negative consequences both in terms of plant development and resistance to environmental challenges. The long-term exposure of plants to unfavorable environmental conditions is accompanied by the transcriptional activation of antioxidant enzymes. Fast ROS production requires the immediate mobilization of the antioxidant defense system which may occur via retrograde signaling, redox-based modifications, and the phosphorylation of ROS detoxifying enzymes. This review aimed to summarize the current knowledge on signaling processes regulating the enzymatic antioxidant capacity of plants.